Teachers’ language level influence to determine tenth and eleventh grade students’ English proficiency in a public school in Armenia (2016)
Colombian students’ lack of proficiency has been considered as an issue within Colombian Government education framework. For this reason, this project has been done in order to measure this situation. The first step was determining teachers’ help in the process of being bilingual. To do so, some surveys were applied to Normal Superior del Quindio and San Francisco institution from Chinchiná Caldas . The surveys determined that they do not get B1 or B2 because their teachers do not have them either. Nevertheless, another result was that when teachers have a good English level, they do not have a good methodology that can allow effective learning. Also, some teachers were interviewed and they agreed with this problem.